Flexible Interconnection of Graph Transformation Modules - A Systematic Approach - Engels, Gregor; Heckel, Reiko; Cherchago, Alexey (Formal Methods in Software and System Modeling. Essays Dedicated to Hartmut Ehrig on the Occasion of His 60th Birthday)
Modularization is a well-known concept to structure software systems as well as their specifications. Modules are equipped with export and import interfaces and thus can be connected with other modules requesting or providing certain features. In this paper, we study modules the interfaces of which consist of behavioral specifications given by typed graph transformation systems. We introduce a framework for classifying and systematically defining relations between typed graph transformation systems. The framework comprises a number of standard ingredients, like homomorphisms between type graphs and mappings between sets of graph transformation rules. The framework is applied to develop a novel concept of substitution morphism by separating preconditions and effects in the specification of rules. This substitution morphism is suited to define the semantic relation between export and import interfaces of requesting and providing modules.

Konsistenzmanagement von objektorientierten Verhaltensmodellen - Küster, Jochen (Ausgezeichnete Informatikdissertationen 2004)
In der modellbasierten Softwareentwicklung wird ein Softwaresystem durch verschiedene Teilmodelle auf unterschiedlichen Abstraktionsstufen und aus verschiedenen Sichten modelliert. Das Ziel von Konsistenzmanagement im Entwicklungsprozess ist es, eine gewisse Form von Konsistenz der Teilmodelle zu gewährleisten. Da objektorientierte Verhaltensmodelle keine eindeutige formale Semantik haben und sehr unterschiedlich eingesetzt werden, ist ein Konsistenzmanagement dieser Modelle besonders schwierig. In der Arbeit werden sowohl Grundlagen als auch Techniken für ein systematisches Konsistenzmanagement entwickelt und am praktischen Beispiel erprobt.

Dynamic Software Architectures: A Style-Based Modeling and Refinement Technique with Graph Transformations - Thöne, Sebastian
A good architectural design allows to capture the overall complexity of large, distributed systems at a higher level of abstraction. This is especially important for reconfigurable systems where the architectural configuration is subject to (constant) changes at runtime. When designing such a dynamic architecture, the software architect has to bring the functional business requirements and the available communication and reconfiguration mechanisms of the intended target platform in line. As it is a complex task to incorporate these often diverging requirements into the architectural model, we propose a stepwise approach similar to the MDA initiative. We start with a platformindependent model capturing the business requirements and add platform-specific details in a later step. For each level of platform abstraction and associated platform, we define an architectural style which describes the characteristics of the platform. This way, conformance to the architectural style entails consistency with the underlying platform. Besides run-time configurations of components and connections, architectural models also comprise the description of processes that control the communication and reconfiguration behavior. To provide operational semantics, architectural models are formalized as graphs, and architectural styles are formalized as graph transformation systems. UML is added as high-level modeling language on top, and profiles are used to adapt UML to certain architectural styles. Due to the stepwise procedure, we also have to ensure the mutual consistency between models at different levels of abstraction. For this purpose, we define formal criteria which require that both structural and behavioral properties are preserved at the lower level of abstraction. Based on refinement relationships between abstract and platform-specific architectural styles, an algorithm allows to verify that all abstract, business-level behavior can also be realized in the platformspecific architecture and that no new behavior is added. These refinement techniques facilitate a stepwise, platform-consistent development of dynamic software architectures.

Trace-based Debugging and Visualisation of Concurrent Java Programs with UML - Mehner, Katharina
This thesis describes an approach for automated detection of concurrent liveness failures in the execution of Java programs. Concurrent programs are highly prone to failure because of the inherent nondeterminism. Developers of concurrent Java programs are not well supported in detecting concurrency failures, i.e. failures that are due to interactions between multiple threads. These failures are neither well documented nor do tools like debuggers allow developers to identify them at runtime. This thesis analyses and classifies liveness failures, a special kind of concurrency failures, and the associated potentials in Java. A UML statechart is developed that models the interaction of Java threads. Liveness failures and potentials are specified formally in terms of the states controlling the interaction of threads and in terms of the events exchanged by interacting threads. Detection algorithms are developed to identify the specified failures in a program execution. A UML profile extending UML interaction diagrams is developed to visualise the execution of concurrent Java programs and detected liveness failures and potentials. In order to deploy the algorithms and the UML profile, tool support concepts are provided. This involves the specification of a trace format and a tracing method to collect execution data from a running Java program, and the specification of methods to analyse the trace and to visualise the trace and the analysis results. The concepts are implemented in the JAVIS prototype, which consists of a Java tracer with an analysis facility for monitoring liveness in concurrent Java programs, and a plug-in extension to the UML CASE tool Together for importing and displaying concurrent Java traces including failures and potentials.

Dynamic Meta Modeling: A Semantics Description Technique for Visual Modeling Languages - Hendrik Hausmann, Jan
The technique of Dynamic Meta Modeling allows for specifying the semantics of visual modeling languages (like, e.g., the Unified Modeling Language, UML). It is aimed at combining formal rigor (allowing for automated processing of expressions in the language and reasoning about them) with a user-friendly visual notation. We do explicitly exploit the meta modeling paradigm to provide our formalizations within a form known to the expected user base. Technically, DMM uses an innovative combination of elements from denotational and operational semantics together with Graph Transformations. The thesis furthermore introduces a technically richer concept of relations to the Meta Object Facility (MOF). As an extended application example the core semantics of UML Activity Diagrams are formalized within this thesis. Pragmatic guidelines to formulate specifications in DMM and tool support to test the effect of such specifications complete the thesis.

GaN blue photonic crystal membrane nanocavities - Choi, Y.-S.; Hennessy, K.; Sharma, R.; Haberer, E.; Gao, Y.; DenBaars, S. P.; Nakamura, S.; Hu, E. L.; Meier, Cedrik (Applied Physics Letters)

Screening effects in InAs quantum-dot structures observed by photoluminescence and capacitance-voltage spectra - Lüttjohann, Stephan; Meier, Cedrik; Lorke, Axel; Reuter, Dirk; Wieck, Andreas D. (Applied Physics Letters)

Photonic bands in two-dimensionally patterned multimode GaN waveguides for light extraction - David, A.; Meier, Cedrik; Sharma, R.; Diana, F. S.; DenBaars, S. P.; Hu, E.; Nakamura, S.; Weisbuch, C.; Benisty, H. (Applied Physics Letters)

Vertically oriented GaN-based air-gap distributed Bragg reflector structure fabricated using band-gap-selective photoelectrochemical etching - Sharma, R.; Haberer, E. D.; Meier, Cedrik; Hu, E. L.; Nakamura, S. (Applied Physics Letters)

Infrared properties of silicon nanoparticles - Kravets, Vasyl G.; Meier, Cedrik; Konjhodzic, Denan; Lorke, Axel; Wiggers, Hartmut (Journal of Applied Physics)